2001
DOI: 10.1029/2000jd900723
|View full text |Cite
|
Sign up to set email alerts
|

Direct observations of clear‐sky aerosol radiative forcing from space during the Indian Ocean Experiment

Abstract: Abstract. This study presents the regional estimates of the seasonal and diurnal mean broadband (0.3-5.0 •m) clear-sky aerosol radiative forcing at the top of atmosphere (TOA) due to both the natural and the anthropogenic aerosols over the tropical Indian Ocean from 25øN to 25øS. We propose two new methods, the slope method and the differencing method, to obtain clear sky aerosol forcing from solely satellite measurements. The focus of the study is January to March 1997, 1998, and 1999. The TOA clear-sky aeros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
46
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(51 citation statements)
references
References 27 publications
(10 reference statements)
5
46
0
Order By: Relevance
“…Furthermore, observational PM data in different Spanish sites have also shown a decreasing trend in the 2000s (e.g., Barmpadimos et al, 2012;Cusack et al, 2012;Pey et al, 2013;Bennouna et al, 2014;Mateos et al, 2014). This fact can be understood by the effect of the current economic crisis and the implementation of new environmental laws to control the pollution (e.g., Querol et al, 2014). In addition, recent studies have shown that natural aerosols have also decreased in the last decade.…”
Section: Analysis Of Aerosol Properties Over the Iberian Peninsulamentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, observational PM data in different Spanish sites have also shown a decreasing trend in the 2000s (e.g., Barmpadimos et al, 2012;Cusack et al, 2012;Pey et al, 2013;Bennouna et al, 2014;Mateos et al, 2014). This fact can be understood by the effect of the current economic crisis and the implementation of new environmental laws to control the pollution (e.g., Querol et al, 2014). In addition, recent studies have shown that natural aerosols have also decreased in the last decade.…”
Section: Analysis Of Aerosol Properties Over the Iberian Peninsulamentioning
confidence: 99%
“…This is a key quantity in the determination of climate change (e.g., Hansen et al, 1998). Most studies dealing with ARE have focused on discrete wavelengths, whole shortwave (SW) solar radiation spectrum (e.g., Rajeev and Ramanathan, 2001;García et al, 2008;di Sarra et al, 2008;Foyo-Moreno et al, 2014;Mateos et al, 2013a), longwave (LW) radiation (e.g., Panicker et al, 2008;di Sarra et al, 2011;Antón et al, 2014), ultraviolet (UV) interval (e.g., Hatzianastassiou et al, 2004;Kazadzis et al, 2009;Nikitidou et al, 2013), and visible (VIS) range (e.g., Jayaraman et al, 1998;Horvath et al, 2002;Bush and Valero, 2003;Meloni et al, 2003). With regards to surface SW radiative effect (ARE SW ), Di obtained the maximum radiative daily effects for different aerosol types in the central Mediterranean in the period [2004][2005][2006][2007]: −61 W m −2 (desert dust aerosols), −26 W m −2 (urban/industrial-biomass burning aerosols), and −43 W m −2 (mixed aerosols).…”
Section: Introductionmentioning
confidence: 99%
“…21. These strong gradients, including the sharp gradient across the ITCZ, were first noted in measurements made on the pre-INDOEX and INDOEX ship cruises (e.g., Rhoads et al, 1997;Moorthy et al, 1997;Jayaraman et al, 1998Jayaraman et al, , 1999Jayaraman et al, , 2001Satheesh et al, 1998;Naja et al, 1999;Stehr et al, 2002;Quinn et al, 2002;Chand et al, 2001Chand et al, , 2003Kamra et al, 2003;Norman et al, 2003;Nair et al, 2004;Naja et al, 2004), as well as in aircraft observations during INDOEX (e.g., Ramanathan et al, 2001;Reiner et al, 2001;Gabriel et al, 2002a;Pelon et al, 2002;de Reus et al, 2002), and shortly thereafter were corroborated to be a general feature of the broader region based on numerous pieces of evidence, including further in situ observations, satellite retrievals and model simulations (e.g., Rajeev et al, 2000Rajeev et al, , 2004Rajeev and Ramanathan, 2001;Collins et al, 2001Collins et al, , 2002de Laat et al, 2001a, b;Lelieveld et al, 2001;Lawrence et al, 2003a;Minvielle et al, 2004a, b;Moorthy et al, 2005a;Satheesh et al, 2006a, b;Vinoj et al, 2007;Verma et al, 2008). In addition to this generally strong gradient of pollutants in the SAW-ABC, these observations and modeling studies have also shown a very abrupt transition between the polluted NH air masses and more pristine SH air in the MBL at the ITCZ, which can be considered a "chemical ITCZ" …”
Section: Transit Times Lofting In the Itcz And Interhemispheric Exchmentioning
confidence: 99%
“…This, along with weaker absorption by dust than by pollution, results in a more negative TOA DRE in May (Satheesh and Srinivasan, 2002). The aerosol direct solar effect also has large spatial variations over the tropical Indian Ocean (Rajeev and Ramanathan, 2001). The observed TOA solar effect north of the equator is about a factor of 2 greater than that south of the equator, with the minimum effect occurring around the Inter-Tropical Convergence Zone (ITCZ).…”
Section: E Arabian Sea and Northern Indian Oceanmentioning
confidence: 99%